CHURCHES AND PRIVATE EDUCATIONAL INSTITUTIONS AS FACILITATOR OF MONEY LAUNDERING: THE CASE OF NIGERIA - KINGSTON, Kato Gogo (Journal of Advanced Research in Law and Economics, 2017)
There is worldwide concern over the ways in which criminally acquired assets are being concealed, transferred and preserved. Many countries including Nigeria have enacted laws against money laundering; drugs trafficking; and, corruption. The study investigates the association of money laundering through the private schools and churches; and, four independent variables namely: Laws and Regulations, enforcement efficiency, banking compliance and corruption. The multiple regression models of Aldrich (2005), and Fisher (1922) are employed to investigate the association of the variables. The study hypothesize that money laundering in Nigeria is enhanced by the proliferation of churches and private educational institutions by which finances are largely unchecked by the authorities to such degree that defective banking regulations; lack of government control of the funds of private schools and faith groups; inadequate enforceability of anti–money laundering laws; and, corruption are the propelling factors. The study suggests that private schools and churches in Nigeria are facilitating money laundering, corruption and organised crimes. It finds that there are serious loopholes in Nigeria’s money laundering laws which enable criminal assets to be preserved and protected under the auspices of schools and church assets. The study concludes that there is urgent need for the overhaul of the national criminal laws and the regulation of the assets of private schools and churches in such ways that can deprive the criminal concealment of illegally acquired assets.